Banking Management Regarding Operational Risks - Anca – Ioana BUMBENECI (Revista de Management Comparat International)
Banks are functioning in a complex economic environment, which becomes increasingly dynamic whenever the competition gets stronger. The risks implied by the banking activity have a multiple determination, starting from the specific features of their own operations, to the features of the internal and external environment. Under the Basel Agreement, the operational risk is approached depending on the category of events in which it is included. The Basel II Agreement uses three measuring methods: a fixed percentage (15%) of the average anual bank income (over the last three years), a variable percentage (between 12 and 18%) of the gross bank income (corresponding to the category in which the bank is included) and a combined methos based on the validity of the bank income. The operational risk management system involves 4 key-processes: identification, assessment, analysis and control – reduction of the risk. Each key process operates with relatively standardized measures.